Investigation of Emotional Intelligence in Medical Students at Babol University of Medical Sciences Based on the Bar-On Questionnaire - Mohamad Vahdat-lasemi; Mahjoobeh Betyar; Maryam Ghaemi-Amiri (آموزش پزشکی)
Background and Objective: Emotional skills and abilities, commonly known as emotional intelligence, predict individuals' success in life and their ability to cope with stress. Developing a sense of responsibility, leading a happy and vibrant life, handling dangerous situations, and fostering a spirit of cooperation and assistance to others are outcomes of emotional intelligence. It is also a strong predictor of academic progress and success, serving as a fundamental pillar for achieving academic success, which can be enhanced through appropriate methods. Therefore, this study was designed and conducted to study emotional intelligence among medical students. Methods: Given the nature of the subject, the objectives, and the hypotheses of the research, this study is a cross-sectional analytical study with an applied purpose and is descriptive and correlational in terms of research methodology. It assessed the emotional intelligence of Babol University of Medical Sciences medical students during the academic year 1402. The Bar-On Emotional Intelligence Questionnaire was used as the data collection tool. The data were analyzed using SPSS version 26, with a significance level set at 0.05. Findings: A total of 278 medical students from various levels participated in this study. The mean score of the emotional intelligence test and its standard deviation were 321.04 and 4.365, respectively. Conclusion: Achieving a higher level of emotional intelligence components enhances an individual's capacity to accept realities, increases flexibility, improves emotional problem-solving abilities, and aids in coping with stress and impulses. By incorporating emotional intelligence into educational programs, students can be better equipped to handle academic pressures and experience fewer emotional problems and dropout rates.